PEMANFAATAN PEKARANGAN SEBAGAI USAHA PENINGKATAN KETAHANAN PANGAN KELUARGA MELALUI REKAYASA KESUBURAN TANAH DI WILAYAH PESISIR KELURAHAN BUNGKUTOKO KOTA KENDARI - Laode Sabaruddin; Murdjani Kamaluddin; Zulfikar Zulfikar; Nini Mila Rahni; Arsy Aysyah Anas; Wa Kuasa Baka (Universitas Halu Oleo, 2022)
The majority of the population in Bungkutoko Village are fishermen and housewives. The problem encountered in most households in this village is that the yard land has not been utilized for the cultivation of plants that are useful for food availability. In addition, household waste is widely available but has not been maximally utilized as raw material for making planting media for cultivated plants. Therefore, community service activities are carried out to increase community knowledge and skills in utilizing yard land for vegetable crop cultivation in order to support food security through modification of agricultural techniques and soil fertility engineering. The method used is socialization and counselling, then practice or demonstration in the field of how to cultivate vegetables to provide real examples to partners. Partner members are continuously encouraged to always be actively involved and become subjects in this activity accompanied by students and a team of lecturers. The result of community service is that the community is able to apply the yard utilization model because of the increased knowledge and skills of the community about the cultivation of food crops (vegetables) in the yard, and the increased knowledge and skills of the community about soil fertility engineering in the yard/coastal land.